Administrative and Legal Principles of Licensing the Safeguarding Activity of the Ministry of Internal Affairs of Ukraine (Law and Safety, 2020)
The article has an overview character and is focused on the peculiarities of legal regulation of licensing of safeguarding activity. The essence of safeguarding activity has been determined. The concept of licensing the safeguarding activity has been suggested. Legislative acts and bylaws regulating the licensing the safeguarding activity have been provided. Safeguarding activity can be defined as the provision of services for the protection of property and personal security of citizens by business entities. Such provision is carried out on the basis of a license issued by an authorized agency and regulated by the norms of the current law. Licensing of safeguarding activity is a mean of state regulation of economic activity for the provision of safeguarding services by setting requirements for business entities engaged in such activities, and monitoring their compliance both during obtaining a license and in the course of economic activity. The Ministry of Internal Affairs of Ukraine is the agency authorized to review documents for obtaining a license to carry out safeguarding activity.The peculiarities of obtaining a license to provide services for the protection of property, life and health of a person have been established. The specificity of licensing safeguarding activity is due to the increased risk to life and health of employees who perform safeguarding functions at protected facilities and while the protection of individuals.Among the features of licensing safeguarding activity it is necessary to indicate personnel, organizational and technological requirements for safeguarding companies. The list of documents submitted to the Ministry of Internal Affairs of Ukraine by the applicant for a license to provide safeguarding services has been determined. The authors have provided characteristics of qualification requirements to personnel of safeguarding company. The organizational requirements for the licensee have been determined. These requirements consist in the availability and accounting civil contracts for the provision of safeguarding services and the procedure for interaction with the police. Technological requirements establish the list and characteristics of the equipment, which should be used by the safeguarding company in accomplishing the tasks.The authors have provided propositions to amend the current legislation regulating the licensing of safeguarding activity to change the licensing authority.
Keywords: licensing; safeguarding activity; legal regulation; licensing conditions; state regulation